Optimization of Hybrid Battery-Supercapacitor Storage System in Electric Ship Using Multi-Objective Genetic Algorithm - Sreymey Meng; Vita Lystianingrum; Agoes Santoso (International Journal of Marine Engineering Innovation and Research, 2025)
As the marine industry now is running toward the green and more efficient propulsion system, the optimization has also become a primary part of the research. This research study is focusing on the optimal sizing of Hybrid Energy Storage (HESS) in electric ship using Multi-Objective Genetic Algorithm (MOGA). By integrating the battery and supercapacitor (SC), it helps cover the load demand while enhancing a good performance to the ship. This research study is to optimize sizing of HESS with a suitable Energy management System (EMS) to desired the intention of minimize the total cost of HESS and degradation of the battery. The proposed model addresses the complexity of HESS while optimized the distribution of power for both the battery and SC, handling the load condition.